Religious Tourism Attractions at Debre Aron Rock-Hewn Church, Meket District, Northern Ethiopia - Tsegaye Demissie (International Journal of Religious Tourism and Pilgrimage, 2024)
Ethiopia, which has a diverse sacred cultural heritage, has enormous fortunes as far as religious tourism is concerned. Its ancient Christianity has left numerous religious and historical legacies, ranging from architecturally sophisticated sacred monuments to living religious practices. However, the development of these legacies for religious tourism is hindered mainly due to a lack of research and consideration by tourism developers. This study aims to investigate the potential tourism value of Debre Aron Monastery, which is one of the most overlooked religious sites in northern Ethiopia. To this end, the study’s data, which are analysed qualitatively, were collected through literature review, field observation, and interviews. The study reveals that Debre Aron is endowed with significant values that are quite worthwhile for religious tourism and pilgrimage development. Physically, the monastery is established on a spectacular mountain, Debre Daret, which overlooks the lowlands of the upper course of the Tekkezze River. Historically, it has a significant local narrative linked to its founder, Abba Aron, a prominent monk in the 14th century. Aron has been honoured as miraculous by the local Christians because of his spiritual triumph during the struggle he had with the thenkings, who were criticised for their non-Christian practices. In relation to this, it was one of the few monastic centers that marked the then uneasy church-state relationship. Architecturally, Aron’s rockhewn church posesses significant architectural components. The siquret (an aperture) in the roof of the chanting room does not allow rainfall to penetrate but allows sunlight. This feature, among others, is a unique architectural tradition of this cave church. The monastery also has preserved ancient sacred treasures, some of which are attributable to Aron. The gudib, which Aron used to excavate his church, is the most sacred treasure that has not only spiritual but also archaeological value in relation to ancient rock-hewn churches in Ethiopia. The monastery’s annual festivity, which falls on September 15th, is an important platform to promote the monastery as a center of religious tourism and pilgrimage. However, these values should be managed and developed for religious tourism purposes by establishing the necessary infrastructure needed both for tourists and local communities.